(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
The age of the knights. Knightly pre-eminence, local societies and powers: new perspectives on the Italian countrysides (11th – 13th centuries) is a two-year PRIN 2022 research project, funded by the European Union – Next Generation EU, which aims to fill the great historiographical gap on the pervasive presence of mounted fighters even in castle and village communities, where they often constituted the eminent social class. The aim here is to illustrate the project contents and objectives, but also the first results of the research path undertaken, which emerged during two seminar meetings held on September 27, 2024, and March 27, 2025.